2007
DOI: 10.1152/ajprenal.00194.2006
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of renal autoregulation

Abstract: The kidney displays highly efficient autoregulation so that under steady-state conditions renal blood flow (RBF) is independent of blood pressure over a wide range of pressure. Autoregulation occurs in the preglomerular microcirculation and is mediated by two, perhaps three, mechanisms. The faster myogenic mechanism and the slower tubuloglomerular feedback contribute both directly and interactively to autoregulation of RBF and of glomerular capillary pressure. Multiple experiments have been used to study autor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

14
189
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 171 publications
(204 citation statements)
references
References 224 publications
(237 reference statements)
14
189
1
Order By: Relevance
“…In contrast, the results of more recent experiments conducted on isolated pulmonary artery myocytes suggested that IP3-releasable and caffeine-releasable calcium stores are virtually completely separate (Janiak et al, 2001). A similar conclusion was made from the experiments performed on in intact precapillary vessels, where agonistinduced [Ca 2+ ]i oscillations were insensitive to the combined action of caffeine and ryanodine (Borisova et al, 2009 We tested our hypothesis that Ca 2+ entry following P2X activation may induce IP3R-mediated Ca 2+ release on RVSMCs, because: (i) P2X receptors mediate sympathetic control and autoregulation of the renal circulation (Malpas and Leonard, 2000;Nishiyama et al, 2000;Bell et al, 2003;Inscho et al, 2003;Cupples and Braam, 2007;Guan et al, 2007a;Surprenant and North, 2009); and (ii) RVSMCs express functional monomeric P2X1 and heteromeric P2X1/4 receptors (Harhun et al, 2010).We found that depolarization of RVSMC induced by selective stimulation of P2X receptors with ab-meATP triggers Ca 2+ release from sub-plasmalemmal SR enriched with IP3Rs but poor in RyRs, similar to direct stimulation of IP3Rs by uniform cell-wide release of IP3 from its 'caged' precursor. The ab-meATP-induced SPCU was significantly reduced by block of VGCCs or depletion of the intracellular calcium stores, indicating that activation of P2X receptors in RVSMCs recruits both voltage-gated Ca 2+ entry and the SR Ca 2+ release to intracellular Ca 2+ mobilization.…”
mentioning
confidence: 59%
See 2 more Smart Citations
“…In contrast, the results of more recent experiments conducted on isolated pulmonary artery myocytes suggested that IP3-releasable and caffeine-releasable calcium stores are virtually completely separate (Janiak et al, 2001). A similar conclusion was made from the experiments performed on in intact precapillary vessels, where agonistinduced [Ca 2+ ]i oscillations were insensitive to the combined action of caffeine and ryanodine (Borisova et al, 2009 We tested our hypothesis that Ca 2+ entry following P2X activation may induce IP3R-mediated Ca 2+ release on RVSMCs, because: (i) P2X receptors mediate sympathetic control and autoregulation of the renal circulation (Malpas and Leonard, 2000;Nishiyama et al, 2000;Bell et al, 2003;Inscho et al, 2003;Cupples and Braam, 2007;Guan et al, 2007a;Surprenant and North, 2009); and (ii) RVSMCs express functional monomeric P2X1 and heteromeric P2X1/4 receptors (Harhun et al, 2010).We found that depolarization of RVSMC induced by selective stimulation of P2X receptors with ab-meATP triggers Ca 2+ release from sub-plasmalemmal SR enriched with IP3Rs but poor in RyRs, similar to direct stimulation of IP3Rs by uniform cell-wide release of IP3 from its 'caged' precursor. The ab-meATP-induced SPCU was significantly reduced by block of VGCCs or depletion of the intracellular calcium stores, indicating that activation of P2X receptors in RVSMCs recruits both voltage-gated Ca 2+ entry and the SR Ca 2+ release to intracellular Ca 2+ mobilization.…”
mentioning
confidence: 59%
“…Although M3 receptors are linked to a Gq/11/PLC/IP3/Ca 2+ signalling pathway, we hypothesized that in contrast to cardiac muscle, excitation-contraction (E-C) coupling in smooth muscle occurs by Ca 2+ entry through VGCCs, which evokes IP3R-mediated Ca 2+ release via CICR mechanism. This hypothesis needs to be tested in vascular myocytes regulated by ionotropic receptors, which are not coupled to the Gq/11-GTP/PLC/IP3 system.Taking into account the importance of ionotropic P2X receptors (Burnstock, 2007;Surprenant and North, 2009) in the regulation of renal circulation (Malpas and Leonard, 2000;Inscho et al, 2003;Cupples and Braam, 2007;Guan et al, 2007a), we tested our hypothesis on RVSMCs, which, as we have recently demonstrated, express functional monomeric P2X1 and heteromeric P2X1/4 receptors (Harhun et al, 2010). We found that depolarization of RVSMCs following P2X receptor activation induces IP3R-mediated Ca 2+ release from sub-plasmalemmal ('junctional') sarcoplasmic reticulum (jSR), which is activated mainly by Ca 2+ influx through VGCCs.…”
mentioning
confidence: 95%
See 1 more Smart Citation
“…32 The renal autoregulatory response is coordinated by two mechanisms: myogenic response and tubulo-glomerular feedback. 33 On the basis of the results of our experiments in DS rats, ARB seems to improve the renal autoregulatory response in parallel with endothelial function. The endothelium has a central role in early functional adaptations to hypertension.…”
Section: Ds-h Ds-l Ds-h-tel Ds-h-mentioning
confidence: 74%
“…Th us, furose mide decreased renal O 2 Ex and improved renal oxygenation as renal blood fl ow was not signifi cantly aff ected by the diuretic. Interestingly, GFR decreased by 12 % with furosemide, which could be explained by an increased delivery of sodium to the distal tubules activating the tubuloglomerular feedback mechanism, eventu ally inducing a constriction of the aff erent arterioles and a decrease in GFR [17]. Th is mechanism could explain the fi ndings of Lassnigg et al, who demonstrated in low-risk cardiac surgery patients with normal renal function that furosemide lowered creatinine clearance postoperatively [18].…”
Section: Eff Ects Of Diureti Cs On Renal Oxygenation In the Postoperamentioning
confidence: 99%